A productivity index model for Philippine Engineering Schools - Matias, Aura C. (Philippine Engineering Journal)
The measurements of the productivity of education systems necessarily rely on numerous interrelated aspects and judgements. This paper illustrates an application of the concepts of multi-attribute utility evaluation of productivity for engineering educational institutions based on the assessment of deans of engineering schools/colleges in the Philippines. The school administrators selected for the surveys and elicitation process were from school that offered both B.S. Chemical and B.S. Mechanical Engineering undergraduate programs. Fifteen schools from the total list of 196 engineering schools (based on the official list of recognized engineering schools as of 1987, Technical Panel for Engineering Education) responded to the survey. Five of these respondents were selected for the further development and assessment of the proposed model. Seventeen quantitative and qualitative measures of productivity were identified. The assessment produced an additive multi-attribute function with a bilinear sub-model for quality and quantity of research outputs. The model was tested using 4 engineering schools in the National Capital Region. The model was partially successful in evaluating the performance of the selected schools.